Comparative analysis of pre-filled syringes and traditional equipment for nursing activities - Grochans, Elżbieta (Nursing Problems / Problemy Pielęgniarstwa, 2013)
One of therapeutic nursing activities is administering drugs through various routes, including injections. A properly performed injection requires adherence to rules, the knowledge of procedures, as well as the choice and use of suitable equipment. A pre-filled syringe is a modern tool for drug administration. This is a combination of a syringe and an ampoule filled with a drug, thanks to which a medicine can be given immediately, and without the necessity of using the drug preparation procedure by health care workers. The use of pre-filled syringes is advantageous both to patients, medical staff, and medical centres. Since the time of drug preparation procedure is shortened, the stress experienced by patients is lower. What is more, the use of pre-filled syringes saves plenty of time, and is safer both for patients and health workers, especially if predefined needles and automatic needle guard (ANG) are applied (fewer manual adjustments — a lower risk of infection). Also the possibility that a patient will be administered improper dose of a medicine as a result of its loss during the preparation is eliminated. The exposure to risks and complications, which may occur while preparing medicines, is reduced, so patients do not have to pay additional financial and health costs. Moreover, the employment of pre-filled syringes is more economic and environmentally friendly due to the fact that significantly less municipal and medical waste is produced during giving injections. Nursing Topics 2013; 21 (1): 98–107